Pengaruh Citra Merek, Harga, dan Sertifikasi Halal Terhadap Loyalitas Merek Pada Zoya - Hanifah Hanifah; Lily Puspita Sari (Universitas Pembangunan Nasional Veteran Jakarta, 2022)
The growth of the halal industry sector in Indonesia in recent years is experiencing very fast growth, one of which is the halal fashion industry. Seeing the rapid development of the Muslim fashion business will certainly make the competition of the business tight, one of the brands that experience competition is Zoya. In 2016 Zoya received the top brand award, but the percentage value of the brand survey on Zoya experienced instability in the next few years with the meaning that zoya consumers had decreased and resulted in a decrease in brand loyalty. Based on this, this study aims to determine the influence of brand image, price, and halal certification on brand loyalty to Zoya. Using quantitative research methods with secondary and primary data and a sample of 404 respondents who fit the criteria. The data analysis techniques used in this study are classical assumption testing, multiple linear regression, and hypothesis testing. The results obtained in this study are that the brand image variable has a significant effect on brand loyalty, then the price variable affects brand loyalty, and the halal certification variable affects brand loyalty. Furthermore, results are obtained simultaneously or simultaneously that the variables of brand image, price, and halal certification have a significant effect on brand loyalty.